The role of instability rehabilitative resistance training for the core musculature - Behm, D.; Drinkwater, E. J.; Willardson, J. M.; Cowley, P. M. (Strength and Conditioning Journal, 2011)
Neuromuscular training of the spinal stabilizing musculature is relevant for lower back pain prevention and treatment. Instability resistance exercises promote cocontractions, increasing joint stability. of greatest importance to joint stability is not necessarily strength or endurance but motor control. Dynamic provocative calisthenic exercises may improve core stabilizing functions. Higher core muscle activation is possible with stable ground-based exercises. Performing resistance exercises on unstable surfaces may have benefits in joint injury prevention and improving balance; however, strength gains could be compromised. Higher levels of dynamic stabilization may be recommended with rehabilitation but should only be one component of a periodized plan.